2016
DOI: 10.1177/1744987116643232
|View full text |Cite
|
Sign up to set email alerts
|

Guest Editorial: Promoting cultural competency in the nursing care of LGBT patients

Abstract: The eight principles of nursing practice developed by the professional nursing union, the Royal College of Nursing (RCN) of the United Kingdom, in collaboration with the UK nursing regulatory body, the Nursing and Midwifery Council, and the UK government's Department of Health for England set out 'what patients, colleagues, families and carers can expect from nursing'. Patients, members of the public and healthcare staff were involved in developing the principles. They describe what safe and effective nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…This places an unfair burden on LGBTI + individuals, particularly young people. Although positive attitudes among nurses towards LGBT + people appear to be improving (Dorsen, 2012; Lim & Hsu, 2016), heterosexist practices are still commonplace, with some nurses mistakenly believing that a person's sexual orientation or gender identity is not relevant to the care they should provide (Beagan et al., 2012; Fish & Evans, 2016). These are practices that, no doubt, contribute to LGBT + individuals’ sense of invisibility within services and that can limit the potential for a therapeutic alliance to be developed (Beagan et al., 2012; Stewart & O'Reilly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This places an unfair burden on LGBTI + individuals, particularly young people. Although positive attitudes among nurses towards LGBT + people appear to be improving (Dorsen, 2012; Lim & Hsu, 2016), heterosexist practices are still commonplace, with some nurses mistakenly believing that a person's sexual orientation or gender identity is not relevant to the care they should provide (Beagan et al., 2012; Fish & Evans, 2016). These are practices that, no doubt, contribute to LGBT + individuals’ sense of invisibility within services and that can limit the potential for a therapeutic alliance to be developed (Beagan et al., 2012; Stewart & O'Reilly, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for including issues around care for SMW in medical, nursing and allied professional training curricula. A recent review of UK issues around nursing care [43] concluded that, although a number of studies internationally had investigated LGBT nursing care and how it could be introduced into the nursing curriculum, there were no recent UK studies. There was little attention paid to LGBT patients’ needs in many university nursing programmes, resulting in nurses being less than confident when nursing LGBT patients [43].…”
Section: Implications and Recommendations For Practitionersmentioning
confidence: 99%
“…A recent review of UK issues around nursing care [43] concluded that, although a number of studies internationally had investigated LGBT nursing care and how it could be introduced into the nursing curriculum, there were no recent UK studies. There was little attention paid to LGBT patients’ needs in many university nursing programmes, resulting in nurses being less than confident when nursing LGBT patients [43]. Concepts of homosexuality were difficult for nurses who were not being exposed to SMW, because SMW were not coming out in a nursing context.…”
Section: Implications and Recommendations For Practitionersmentioning
confidence: 99%
“…Tüm sağlık profesyonellerinin her bir basamağın farkına varabilmesi ve bu farkındalıklarını eyleme dönüştürebilmesi önemlidir (39) . Kesintisiz sağlık bakımı hizmeti sunan hemşireler, bakım uygulamalarını eşitlik ve adalet ilkeleri doğrultusunda, bireyin onuruna, eşsizliğine ve bütünlüğüne olan inancı ile gerçekleştirmektedir (40,41) . Hemşirelik, sağlık hizmetinin yaş, cinsiyet, ırk, inanç, kültür, cinsel yönelim, görüş ayrımı yapılmaksızın herkese eşit bir şekilde sunulmasını savunmaktadır (40) .…”
Section: Transseksüel Bireylerin Sağlık Bakım Gereksinimleriunclassified
“…Bu ilkeler, her bireyin olduğu gibi LGBT'li bireylerden oluşan topluluğun da sağlığını koruma ve geliştirmesini aynı zamanda kaliteli bir sağlık bakım hizmeti almalarını desteklemektedir. Bu açıdan bakıldığında, hemşireler, transseksüel bireylerin bakımının sunumunda önemli bir pozisyonda bulunmaktadırlar (41) .…”
Section: Transseksüel Bireylerin Sağlık Bakım Gereksinimleriunclassified